Patient‐reported outcomes in Huntington's disease: Quality of life in neurological disorders (Neuro‐QoL) and Huntington's disease health‐related quality of life (HDQLIFE) physical function measures. Issue 7 (27th May 2017) - Carlozzi, Noelle E.; Ready, Rebecca E.; Frank, Samuel; Cella, David; Hahn, Elizabeth A.; Goodnight, Siera M.; Schilling, Stephen G.; Boileau, Nicholas R.; Dayalu, Praveen
ABSTRACT: Background : There is a need for patient‐reported outcome measures that capture the impact that motor impairments have on health‐related quality of life in individuals with Huntington's disease. Objectives : The objectives of this study were to establish the reliability and validity of new physical functioning patient‐reported outcome measures in Huntington's disease. Methods : A total of 510 individuals with Huntington's disease completed 2 Quality of Life in Neurological Disorders (Lower Extremity Function and Upper Extremity Function) and 3 Huntington's Disease Health‐Related Quality of Life (Chorea, Speech Difficulties, and Swallowing Difficulties) measures. Clinician‐rated and generic self‐report measures were also administered. Results : Reliabilities for the new patient reported physical functioning measures were excellent (all Cronbach's α > .92). Convergent, discriminant validity and known group validity was supported. Conclusions : The results provide psychometric support for new patient‐reported physical functioning measures and the fact that these measures can be used as clinically meaningful endpoints in Huntington's disease research and clinical practice. © 2017 International Parkinson and Movement Disorder Society